Gemeinschaftsdiagnose im Frühjahr 2014 - Oliver Holtemöller; Axel Lindner (Wirtschaftsdienst, 2014)
Die Gemeinschaftsdiagnose prognostiziert für Deutschland in diesem und im nächsten Jahr einen Aufschwung, den vor allem die Binnennachfrage trägt. Die Wirtschaftsforschungsinstitute befürchten allerdings, dass sich ein Konjunktureinbruch in Russland negativ auf das deutsche Wachstum auswirken könnte. Von einem fl ächendeckenden Mindestlohn werden vor allem ungünstige Entwicklungen bei der Zahl der Erwerbstätigen erwartet. – – In 2014 and 2015 the German economy will, according to the joint economic forecast, be in an upswing that is mainly driven by strong internal demand. The institutes assess the risks coming from a possible slump of the Russian economy. Simulations with macroeconometric models show that Germany is more affected than other large economies in Europe such as France and Italy. The new minimum wage is a further risk for the German economy that it is diffi cult to assess. According to this forecast, the minimum wage will, when it comes into effect in 2015, mainly have an adverse effect on employment. Since in general only jobs with low productivity will be lost, the effect on production will be markedly smaller.
Keywords: C5; E2; J3; 330; Konjunktur; Konjunkturprognose; Deutschland